2008
DOI: 10.17221/427-pse
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative protection in wheat varieties under severe recoverable drought at seedling stag

Abstract: The antioxidative protection in leaves of four winter wheat (Triticum aestivum L.) varieties with different field drought resistance was studied under severe recoverable soil drought at seedling stage by withholding irrigation for 7 days (57-59% leaf water deficit) followed by rewatering. A 3-fold raise in electrolyte leakage and a sharp increase in proline accumulation corresponded to drought severity. Hydrogen peroxide content and catalase (CAT) activity were maintained low under stress. Peroxidase (GPX) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 17 publications
7
61
1
1
Order By: Relevance
“…These results are in agreement with those of other researchers (Wu et al, 2006), who reported that the activities of SOD, POD, CAT, APX and GR increased under drought stress. Plant cells stimulate different antioxidant enzymes such as CAT, POD, SOD and APX that eliminate these reactive free radicals or suppress their formation (Simova-Stoilova et al, 2008). These results suggest that the activities of SOD, POD and CAT, and contents of H 2 O 2 and MDA are the most important traits for plants' ability to survive under drought stress (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those of other researchers (Wu et al, 2006), who reported that the activities of SOD, POD, CAT, APX and GR increased under drought stress. Plant cells stimulate different antioxidant enzymes such as CAT, POD, SOD and APX that eliminate these reactive free radicals or suppress their formation (Simova-Stoilova et al, 2008). These results suggest that the activities of SOD, POD and CAT, and contents of H 2 O 2 and MDA are the most important traits for plants' ability to survive under drought stress (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…4). CAT plays an important role in moving and scavenging hydrogen peroxide produced in peroxisomes and thus reduces the destructive effects of active oxygen strains (Simova-Stoilova et al, 2008). An experiment determined that increased catalase enzyme activity was effective in boosting resistance to drought stress in corn (Moussa and Abdel-Aziz, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Control of ROS accumulation and detoxification are key processes during abiotic stress phases, which play critical role for yield stability [10]. As ROS protection is common mechanism mobilized in many abiotic stresses including drought [126][127][128][129], heat [10,115,125,130,131] and their combination [122,132], ROS scavenging enzymes and compounds are good candidates for enhanced protection to multiple stress situations. Higher tolerance to drought and/or heat is associated with concerted up-regulation of key detoxifying enzymes in several crop species/varieties leading to better ROS protection along with stability of key metabolic processes like photosynthesis [132] and maintenance of the alternative mitochondrial respiration [123].…”
Section: Leaf Morphology and Physiologymentioning
confidence: 99%